Penerapan Pendekatan STEAM untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika Siswa Kelas VIII D SMPN 23 Balikpapan - Safrine, Dian Putri (Postulat : Jurnal Inovasi Pendidikan Matematika, 2024)
Minimum math problem-solving skill was discovered among 8th-grade students of class D SMPN 23 Balikpapan based on their Mid-Term Exam and daily quizzes results.This research aims to improve their mathematical problem-solving skills by applying the STEAM approach. To test the hypothesis that applying the aforementioned approach results in improving math problem-solving skills, test of problem-solving skills, observation sheets and student response questionnaires were employed through classroom action research consisiting of planning, action, observation and reflection. The test result suggests that the percentage of math problem solving skills of the students increased by 33% in cycle 1 to 50% in cycle 2 and 78% in cycle 3. The observation and student response questionnaires results both indicate satisfying remarks. On this basis, applying the STEAM approach should be taken into account when improving the mathematics problem solving skills for 8th-grade students of class D in SMPN 23 Balikpapan.